Market potential analysis of selected vegetables in Southern Mindanao - Esmeralda, Denmark C.
This study was conducted to analyze the market potential of selected vegetables such as ampalaya, cabbage, eggplant and tomato in Southern Mindanao. In the course of the study, a theoretical framework on quantity demand and supply was formulated which served as the basis of the empirical model employed. In addition, elasticities were also derived as the main tool in determining a market potential for the studied vegetables. Furthermore, a combination of qualitative and quantitative method was used in the making and analysis of the study. The main constraint of the study, however, was data unavailability. Finally, the demand and supply of selected vegetables in Southern Mindanao, from 1990-2001, were assessed; the major demand and supply areas of the selected vegetables were identified; the demand and supply elasticities were examined;and presented recommendations for further study were then drawn.